2013
DOI: 10.1007/s12160-013-9515-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adherence to Medication in Stroke Survivors: A Pilot Randomised Controlled Trial

Abstract: A simple, brief intervention increased medication adherence in stroke survivors, over and above any effect of increased patient contact or mere measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 29 publications
3
115
0
Order By: Relevance
“…Results on the main outcome measure are fully reported in the simple effects article (O'Carroll et al, 2013). In brief, the Intervention group had higher overall adherence than the Control group on all MEMS measures (percentage of total doses taken: Intervention group mean 99% versus Control 94%, 95% CI for difference (-1.6, 9.0); percentage of days correct dose taken: Intervention group mean 99% versus Control 93%, 95% C.I.…”
Section: Primary Outcome Measure -Mems Electronic Pill Bottlementioning
confidence: 99%
“…Results on the main outcome measure are fully reported in the simple effects article (O'Carroll et al, 2013). In brief, the Intervention group had higher overall adherence than the Control group on all MEMS measures (percentage of total doses taken: Intervention group mean 99% versus Control 94%, 95% CI for difference (-1.6, 9.0); percentage of days correct dose taken: Intervention group mean 99% versus Control 93%, 95% C.I.…”
Section: Primary Outcome Measure -Mems Electronic Pill Bottlementioning
confidence: 99%
“…Of these, 18 articles concerned 15 studies with a patient population and stated that an implementation intention had been used [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Two articles were excluded as they described the development of an intervention, an RCT protocol and its feasibility testing [63,64].…”
Section: Resultsmentioning
confidence: 99%
“…The four included studies (reported in five articles) concerned the evaluation of the effectiveness of an if-then plan on i) medication adherence in epilepsy [51] and stroke [53,65], ii) improving exercising and behavioural change in people with chronic back [60], and iii) improving physical activity in obese older adults [66]. Table 2 outlines a summary of the interventions employed in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one study investigated impact of physician-led counselling following first stroke/transient ischaemic attack (TIA). This UK RCT included 62 individuals, with high risk of bias overall 21 (table 3). At 3 months, adherence to antihypertensive medication was higher in the intervention group for doses taken on schedule (ie, mean difference, 9.8%; 95% CI (0.2 to 16.2); p=0.048).…”
Section: Patient Counsellingmentioning
confidence: 99%